Optimization of Indonesian Telematics Smes cluster: Industry 4.0 challenge - TOSIDA, E.T; WAHYUDIN, I; ANDRIA, F; SANURBI, A.D; WARTINI, A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this research is to explain the optimization process of the formation of the Indonesian telematics SMEs cluster. The cluster optimization process is carried out by partitioning around Medoids (PAM) and Fuzzy C-Means (FCM). The data used is the data of SMEs telematics services in Indonesia according to the National Economic Census (SUSENAS) data in 2006 Indonesian Central Bureau of Statistics (CBS). The 2006 data usage is caused by the SUSENAS 2016 not yet released by Indonesian CBS. The cluster of Indonesian telematics SMEs was validated using the Silhouette Coefficient which resulted in a value of upper than 0.99.